Acute myocardial infarction caused by embolisation of an intra-cardiac tumour. (22nd June 2015) - Mostafa, Ashraf; Briasoulis, Alexandros; Schreiber, Theodore
Abstract: This report describes a rare case of left main coronary artery occlusion caused by embolisation of an intra-cardiac tumour in an 11-year-old patient. The patient presented with severe chest pain with ST-segment depression in the inferolateral leads with evidence of decreased left ventricular function, anterior-apical hypokinesis, and a pedunculated mass attached to the mitral valve. An urgent cardiac catheterisation was performed, which revealed near-complete obstruction of the left anterior descending coronary artery. Transcatheter aspiration of the embolic material was successfully performed. The final pathological examination revealed an inflammatory myofibroblastic tumour, which is a rare benign tumour, characterised by the proliferation of myofibroblasts and inflammatory cell infiltration.